2022
DOI: 10.3389/fonc.2022.746896
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Long Non-Coding RNA ASAP1-IT1 in Progression of Hepatocellular Carcinoma

Abstract: The long non-coding RNA (lncRNA) ASAP1-IT1 has been recently shown to aberrantly increase in ovarian and bladder cancer, while its role in other malignancies remains unexplored. This study was to characterize the expression and assess the potential role of ASAP1-IT1 in hepatocellular carcinoma (HCC). Fifty-four paired HCC and histologically normal tissues were obtained from HCC patients. Human HCC cell lines (HepG2, Huh7, SMMC-7721, and BEL-7402) and a normal liver cell line (LO2) were used for in vitro studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It also acts as a biomarker of HCC and mediates its progression ( Huang et al, 2021a ). The significant downregulation of miR-221 following CUR and BBR treatment, as well as the enhanced effect of CUR-BBR combination therapy, suggests a pivotal role of miR-221 in the inhibitory effects of CUR-BBR on HCC progression, which is consistent with a previous study ( Liu et al, 2022a ). Importantly, our results showed that miR-221 overexpression partially reversed the CUR-BBR-mediated decrease in HEPG2 and Huh7 cell survival, which is the first confirmation that the anticancer effect of CUR-BBR is mediated by the miR-221 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…It also acts as a biomarker of HCC and mediates its progression ( Huang et al, 2021a ). The significant downregulation of miR-221 following CUR and BBR treatment, as well as the enhanced effect of CUR-BBR combination therapy, suggests a pivotal role of miR-221 in the inhibitory effects of CUR-BBR on HCC progression, which is consistent with a previous study ( Liu et al, 2022a ). Importantly, our results showed that miR-221 overexpression partially reversed the CUR-BBR-mediated decrease in HEPG2 and Huh7 cell survival, which is the first confirmation that the anticancer effect of CUR-BBR is mediated by the miR-221 pathway.…”
Section: Discussionsupporting
confidence: 92%
“…lncRNA ASAP1-IT1 (the intronic transcript 1 (IT-1) of ArfGAP with SH3 domain, ankyrin repeat and PH domain 1 (ASAP1)) is known to correlate with the overall survival of ovarian cancer patients [78]. Liu et al [67] reported lncRNA ASAP1-IT1 upregulation in HCC tissue samples (54 patients) compared to matched histologically normal liver tissues. Moreover, an inverse correlation between lncRNA ASAP1-IT1 levels and patient overall survival was observed.…”
Section: Lncrnasmentioning
confidence: 99%